Sex difference in long-distance open-water swimming races - does nationality play a role? - Nikolaidis, P. T.; de Sousa, C. V.; Knechtle, B. (Research in Sports Medicine, 2018)
In open-water swimming events with non-elite swimmers held in the USA, but not in Europe, women were faster than men. We examined the sex difference in elite long-distance open-water swimming races and the role of nationality by investigating 7,468 swimmers competing in 5 km, 10 km and 25 km FINA races held between 2000 and 2016. More men participated in 10 km and 25 km than in 5km races. Men were faster than women and the sex difference was similar in all race distances. Swimming speed was faster for 5km than for 10km, which in turn was faster than 25km. There was a major effect of nationality on swimming speed at 5 km and 10 km, but not at 25km. No dominance of a particular nationality was observed for all race distances. In summary, men were faster than women in all FINA race distances from 5km to 25km but nationality played no role in the sex difference.